Development of a fast and user-friendly cryopreservation protocol for sweet potato genetic resources - Wilms, Hannes; Fanega Sleziak, Natalia; Auweraer, Maarten van der; Brands, Martijn; Verleije, Matthijs; Hardeman, Dirk; André, Edwige; Panis, Bartholomeus (Springer, 2020)
Sweet potato (Ipomoea batatas) is one of the ten most important staple crops and provides a livelihood for many people around the globe. To adapt to ever-changing circumstances farmers and breeders need to have access to a broad diversity of germplasm. This study focuses on the development of a cryopreservation protocol that allows the long term storage of different sweet potato cultivars. For this, a droplet vitrification protocol was optimized, comparing several parameters; preculture method (0.3 M sucrose vs no preculture); meristem position (axillary vs apical); plant age (3 to 9 weeks); regeneration medium (MS + 2.22 µM BA, Hirai and MS); and length of loading solution treatment (20 to 360 min). Two months after cryopreservation, the regeneration rates of the meristems were compared, which resulted in significant differences for the preculture method, meristem position and loading solution. With these new insights an optimized droplet vitrification protocol was developed with the following parameters: use of 3–9 week old axillary meristems, no preculture phase, 20 min LS treatment, 30 min PVS2 treatment, exposure to liquid nitrogen by droplet vitrification, warming treatment in RS for 15 min, 1 day 0.3 M sucrose recuperation culture, 1 month MS + 2.22 µM BA followed by 1 month of MS cultures. This protocol was subsequently tested on 10 representative accessions resulting in a post cryopreservation regeneration rate of more than 40% for 70% of the tested cultivars, showing that this protocol could be implemented for a large portion of existing sweet potato collections.